The Influence of Loan Funds and Financial Literacy on the Business Sustainability of MSMEs in East Bogor District - Widyantini, Dian; Boer, Adlinsyah (PT. Anagata Sembagi Education, 2024)
This research aims to analyze the influence of loan funds and financial literacy, as independent variables, on the business sustainability of MSMEs in East Bogor District. The sample size for this research was determined to be 100 respondents, who are MSME entrepreneurs in the region. The sampling method employed was non-probability sampling. Multiple linear regression analysis was used as the analysis method, which included instrument testing and classical assumption testing stages, utilizing SPSS version 25 for Windows. The results of the t-test indicate that both independent variables—loan funds (X1) and financial literacy (X2)—have a positive and significant impact on the business sustainability of MSMEs (Y) in East Bogor District. With a coefficient of determination, R Square (R²), of 0.588, it can be concluded that the business sustainability of MSMEs is explained by these two independent variables by 58.8%, while the remaining 41.2% is explained by other factors not examined in this study.